Meningkatkan Kualitas Kinerja Guru Sekolah Dasar Melalui Supervisi Akademik Kepala Sekolah - Lucia A. M. Patti; Fransiska R. Korompis (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research is to see how supervision can assist teachers in developing their ability to manage the learning process in order to achieve learning objectives. The research design refers to the research design conducted by Kemmis and Taggart. This study describes how a learning technique is applied and how the desired results can be achieved. The spiral model starts from planning, action, observation and reflection, then re-planning for the next cycle. The techniques used include observation, interviews, and documentation. The research objective is to improve teacher performance through the supervision of the principal at Madrasah Ibtidaiyah Al-Mujahirin Bitung. The results of the first cycle describe the teacher's performance by 56.9% with a teacher success rate of 30% and an increase in the second cycle of teacher performance by 93.7% with a teacher success rate of 100% or all teachers succeed in this second cycle. Based on the results of the research conducted, it can be said that the use of principal supervision can improve teacher performance at Madrasah Madrasah Ibtidaiyah Al-Mujahirin Bitung.